Site specific agriculture (Indian Journal of Arid Horticulture, 2020)
An agricultural production system is the consequence of a complex interaction of seed, water and agro- chemicals together with fertilizers and pesticides. Therefore, careful management of all inputs is imperative for the sustainability of such complicated system. The focal point on enhancing the productiveness barring thinking about the ecological impacts of the enter resources has resulted into environmental degradation. Increasing environmental cognizance of the widespread public is necessitating us to regulate agricultural management practices for sustainable conservation of natural sources such as water, air and soil quality, whilst staying economically profitable. The productivity can be elevated except any detrimental effect by using maximizing the aid enters efficiency. It is also certain that availability of labour for agricultural recreation is going to be in quick grant in future. The time has now arrived to carry statistics technology and agricultural science together for extended financial and environmentally sustainable crop production. This offers start to Precision Agriculture or Precision Farming or we also coined this as Site Specific Agriculture. In precision agriculture well timed collection and analysis of the spatial and temporal variant data of crops, soils and surroundings is important. This can be finished by means of new emerging statistics applied sciences such as Global Positioning System (GPS), Geographical Information System (GIS), remote sensing,
Keywords: agricultural; remote sensing; Geographical